THE EFFECT OF SN DOPANT ON THE ELECTRICAL PROPERTIES OF THIN FILMS ZNO GROWED BY DC-UNBALANCED MAGNETRON SPUTTERING - Novi Hendri, Yasni
This research is purpose to study the effect of 3% Sn doping on ZnO materials and see the electrical properties produced and their potential as optoelectronics. Sn: ZnO (SZO) is grown at RT temperature (SZO-RT) and compared with pure ZnO with the same deposition temperature. Furthermore, SZO has been grown for other deposition temperatures, 1500C (SZO-150), and 2500C (SZO-250). In this studt, the deposition technique used DC-Unbalanced Magnetron Sputtering. Each sample was characterized using by Scanning Electron Microscopy (SEM ,Photoluminescence (PL) and UV-Vis spectroscopy to analyze morphology, crystal defects, bandgap energy and other optical properties, respectively. Furthermore, I-V measurements were also performed to see the response of the sample to light when illuminated by a 70 Watt halogen lamp and determine the value of the current produced. Sn doped ZnO has been successfully grown marked SEM-EDX were obtained homogeneous ZnO and SZO (SZO-RT, SZO-150, and SZO-250) morphologies and smoother surface images after doping Sn. In the room temperature deposition, spectrum photoluminescence shows that SZO has a higher oxygen void density (Vo) than ZnO. Vo's height plays an important role in sensitizing thin films. Based on I-V measurements the sensitivity of SZO is higher than ZnO. Vo also affects the bandgap value which causes the Burstein-Moss effect. UV-Vis spectroscopy showed that at room temperature there was a shift in bandgap value after Sn doping which was 3.37 eV (ZnO) and 3.40 eV (SZO) while the transmittance curve showed that SZO was more transparent than ZnO. SZO at deposition temperature RT, 1500C and 2500C, based on I-V characteristics there is an increase in sensitivity as you hear the increase in deposition temperature. SZO bandgap energy at deposition temperature of deposition RT, 1500C and 2500C are 3.40 eV, 3.33 eV and 3.29 eV, respectively. These results indicate that Sn doping has the potential to be used as an optoelectronic device.